Autonomous experimental studies resistojet with two autonomous heating elements for nanosatellites - V. N. Blinov; V. V. Kositsyn; A. I. Lukyanchik; P. V. Stepen; P. S. Yachmenev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2023)
The purpose of the work is to conduct autonomous experimental studies of an resistojet with two autonomous heating elements with a diameter of 4 mm. As a result of experimental studies of the resistojet, the heating dynamics of the micromotor structure and the working fluid (isobutane) in the power range from 5 W to 60 W is determined. Experimental studies have shown the possibility of using the proposed resistojet design with two autonomous heating elements not only on small spacecraft, but also on micro- and nanosatellites under conditions of limited on-board energy.